Peningkatan Infrastruktur Transportasi dalam Mendukung Kawasan Strategis Pariwisata Nasional Pulau Rupat - Rafli, Mohammad; Yulianty, Meisye (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
Transportation is a very important component in supporting the development of tourism areas, especially in providing accessibility. Rupat Island, Bengkalis Regency has been designated as a National Tourism Strategic Area based on Government Regulation Number 50 of 2011 concerning the National Tourism Development Master Plan for 2020 – 2025. In reality, Rupat Island is not yet supported by adequate modes of transportation and does not have good connectivity. This research aims to describe the transportation conditions of Rupat Island and the expected infrastructure needs so that it can increase the economic growth of the Rupat Island area. The analysis was carried out using a qualitative descriptive method approach resulting from primary and secondary data processing. Data collection was carried out through field observations, interviews and literature review. The research results show that Rupat Island requires optimal efforts to improve transportation, namely improving crossing transportation modes, improving port facilities and infrastructure, and improving access roads. Providing transportation modes for Rupat Island requires transportation policy steps in the form of building a new pier, replacing ferries, renovating the terminal building and its facilities to ensure the reliability and durability of the terminal and be able to handle potential future traffic. Apart from that, it is necessary to improve the access road from the port to the North Rupat tourist area which is a tourist destination.